Support programme for healthcare professionals involved in adverse events in public hospitals in Gauteng - Nkosi, Elizabeth Malefu (University of the Witwatersrand, Johannesburg, 2022)
Background: Adverse events in the healthcare services result not only in administrative and financial costs to the healthcare institution, but also in personal costs to the patients and their families, who are often angry, disappointed, and sad. In the current litigious healthcare climate, relatives, supported by legal advisors, often seek redress as a way of managing their distress. Thus, patients are not the only victims of adverse events. The healthcare professionals that are directly involved often shoulder the blame, sometimes fairly, and sometimes unfairly, while they too need psychological support. A culture of blame in institutions can lead to healthcare professionals involved in an adverse event being marginalised, feeling personally responsible for the event and that they have failed the patient, and they are left to suffer in silence. While anecdotal evidence exists that such stress may lead to negative coping mechanisms, the researcher has not identified any research study conducted in public hospitals in Gauteng, South Africa that identifies and describes the influence that the involvement in an adverse event has on healthcare professionals. Such evidence is required to develop a support programme that could assist healthcare professionals who have been directly involved in adverse events, to minimise the concomitant stress, and to enable these professionals to continue to provide quality care after such an event. Aim: The purpose of this study was to develop, describe, and evaluate the implementation of a support programme for healthcare professionals involved in adverse events in public hospitals. Methodology: A sequential, multimethod research design was used. The study was conducted in five phases. Phase 1 consisted of a scoping review of the international literature that focused on the experiences of the nurses and doctors. The question asked in the scoping review was: What is known from existing literature about the support programmes for healthcare professionals involved in adverse events in clinical settings, and are they effective? Phase 2 involved storytelling that explored the impact of adverse events on involved healthcare professionals. Smith and Liehr’s (2005) methodology was used, that is, healthcare professionals who were directly involved in or affected by one or more adverse events in the public hospitals in Gauteng narrated their experiences. Phase 3 used semi-structured interviews with the managers to explore how best to support health professionals involved in adverse events. Phase 4 involved developing a support programme according to the Wits Trauma Model developed by Eagle, Friedman and Shumkler, from the Psychology Department of the University of the Witwatersrand, in 1993 (Eagle, 2000). Phase 5 focused on confirming and validating the programme to support healthcare professionals involved in adverse events in public hospitals. This phase was subdivided into two sections: Phase 5.1 comprised the Delphi group; and Phase 5.2 comprised the Focus group. In the first round involving the Delphi group, technical data was collected from the experts who validated the programme by means of the survey that was distributed on Research Electronic Data Capture. Concerns arising out of the first round with the Delphi group and that required attention were addressed during the Focus group discussion. Results: Hospitals were not aware of the magnitude of second victimhood and hence the delay in reviewing the structures in place to provide support to those involved. Just (fair) culture principles were not adhered to as there were no guidelines for their implementation, hence the second victims were left traumatised and in isolation following their involvement in adverse events, and they experienced blaming by management instead of being provided with much needed support. Limitations: The limitations to the study include the small sample size during the data collection phases, due to the Coronavirus disease of 2019 pandemic. Due to the restrictions that were implemented it was not possible to contact all the staff as they had been relocated to other healthcare facilities, were absent, or had resigned. Those who were snowballed were no longer at the facilities where they were originally identified, and therefore the researcher was unable to capture their experiences. Objectivity was not maintained as the documents for the Delphi group were hand-delivered, participants were able to identify the researcher, and hence the social desirability concern. The face-to-face encounters made adherence to anonymity impossible. The model components were not practical in terms of the developed programme. Round two of the Delphi group could not be scheduled, thus challenging the study model. Conclusion: The impact of adverse events on healthcare professionals remains an underestimated health concern. Experiences are magnified by unsupportive work environments, and are evident in increased hostility, blaming, fear of punishment, and reputational harm. The second victims require support to enable them to recover and learn from their involvement. The programme was developed, which included the summarised structure and the detailed process for implementation by hospital management on how to manage the adverse events in public hospitals in Gauteng.
A thesis submitted for the Degree of Doctor of Philosophy in Nursing, to the Faculty of Health Sciences, School of Therapeutic Sciences, at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Second victim; Adverse events; Management; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education